Signs and Symbols in the Ati-Atihan Festival of Kalibo, Aklan, Philippines - Coldovero, Nedy; Aguila, Augusto Antonio (JPAIR Multidisciplinary Research, 2020)
Festival, or fiesta in the Philippine context, is the most anticipated every year in the country since it becomes an indelible part of Filipino culture. It is more than just a display of garb and gallantry but is also done to commemorate significant events in local history, to honor the town patron’s feast, or to give thanks for an abundant harvest and blessings received throughout the year. The Ati-Atihan Festival of Kalibo, Aklan, Philippines, was analyzed and interpreted using semiotic analysis. It presented the answers to the various meanings shown in the festival as filmed or videotaped. The paper adopted descriptive-qualitative research employing interpretive criticism. There were various signs found in the festival, which were interpreted to have denotative and connotative meanings and were classified as iconic, indexical, and symbolic. There are activities participated by the whole community such as the Mass, novenas, processions, beauty pageants, and many others as their way to express their gratitude to God. The festival acts as a social leveler as people from all walks of life throughout the world converge and interact with one another during the celebration. The festival has also come a long way from its humble origins of pagan lore to become a tourism spectacle of pomp and pageantry.
Keywords: Social Science; Ati-Atihan Festival; Barter in Panay; Panay Island; signs and symbols; Semiotics; Literature